2012
DOI: 10.1007/s10067-011-1917-9
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of adult-onset Still’s disease with tocilizumab monotherapy: two case reports and literature review

Abstract: Adult-onset Still's disease (AOSD) is a systemic inflammatory disease of unknown etiology. Recently, it has been reported that quite a few cases of refractory AOSD were successfully treated with tocilizumab (TCZ) and corticosteroids were withdrawn in some of these patients. We report two AOSD patients who were treated successfully with TCZ monotherapy; thus, avoiding corticosteroid treatment. Because both of the patients refused to take corticosteroids, we planned to treat them with 8 mg/kg of TCZ monotherapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 25 publications
0
13
0
1
Order By: Relevance
“…Recent studies of patients with adult-onset Still disease complicated by MAS have evaluated the efficacy of the IL-1 receptor antagonist anakinra and the IL-6 receptor tocilizumab. 31,32 Although small case reports have been promising, there is concern that the inhibition of a single cytokine by a biological response modifier may be of limited efficacy for the treatment of the cytokine storm that is present in MAS. Confirmation of the efficacy of these agents awaits larger trials.…”
Section: Rheumatologic Triggermentioning
confidence: 98%
“…Recent studies of patients with adult-onset Still disease complicated by MAS have evaluated the efficacy of the IL-1 receptor antagonist anakinra and the IL-6 receptor tocilizumab. 31,32 Although small case reports have been promising, there is concern that the inhibition of a single cytokine by a biological response modifier may be of limited efficacy for the treatment of the cytokine storm that is present in MAS. Confirmation of the efficacy of these agents awaits larger trials.…”
Section: Rheumatologic Triggermentioning
confidence: 98%
“…Importantly, recent studies of the IL‐6 receptor antagonist tocilizumab found impressive efficacy in systemic JIA, both for treatment of systemic symptoms (fever and rash) and for treatment of chronic arthritis (). No data are available concerning the efficacy of tocilizumab as first‐line therapy in systemic JIA, although case reports of patients with AOSD suggest that this approach might also be effective ().…”
Section: Efficacy Of Il‐6 Blockade In Systemic Jiamentioning
confidence: 99%
“…Sreenath 1 , S. Cherian 1 , G. Antony 1 , U. Mony 2 , P. Shenoy 1 . 1 Centre for Arthritis and Rheumatism (CARE); 2 Molecular Medicine, AIMS, Cochin, India Background: Palindromic rheumatism (PR) although often considered as a benign disease can be severe and resistant to DMARDs in some patients. In these patients it can result in almost daily attacks, migrating from joint to joint resulting in poor quality of life.…”
Section: Thu0575 Efficacy Of Rituximab In Resistant Palindromic Rheummentioning
confidence: 99%